Foundation course perspectives in I-MBBS professional year in a teaching hospital in south India - Harika Annavaram; Cynthia Subhaprada; Praveena Ganapa (BLDE University Journal of Health Sciences)
INTRODUCTION: Foundation course introduces to the new curriculum and tunes thinking to develop the right attitude and aptitude for the MBBS course. It exposes the students with various learning experiences aimed at developing knowledge, skills, and attitude that will assist them in acclimatizing to the new professional environment which would be their milieu for a lifelong career in medical profession. OBJECTIVES: To assess the perspective of I-MBBS professional year students toward the foundation course. METHODOLOGY: A qualitative study was carried out during November–December 2022 among the I-MBBS professional year students. Institutional ethical committee clearance and informed consent were obtained. The demographics of the students and perceptions of the students toward the teaching methods used in foundation course and overall opinion on graduate medical education brought about by competency-based medical education were collected using a prevalidated questionnaire. The responses were reviewed and the themes were identified. RESULTS: One hundred I-MBBS professional year students participated in the study. The preliminary thematic analysis of the data showed that most of the students opined that they gained knowledge about the topics included in the foundation course and were willing to put it in to practice. They also learned about effective communication with patient and family.This learning experience brought about change in attitude toward medical profession. CONCLUSION: Foundation course helps MBBS-I professional year students to have a smooth transition from school to professional course.